Screening for psychosis risk among help‐seeking adolescents: Application of the Italian version of the 16‐item prodromal questionnaire (iPQ‐16) in child and adolescent neuropsychiatry services. Issue 4 (14th March 2018) - Pelizza, Lorenzo; Azzali, Silvia; Paterlini, Federica; Garlassi, Sara; Scazza, Ilaria; Chiri, Luigi Rocco; Poletti, Michele; Pupo, Simona; Raballo, Andrea
Abstract : Aim: The 16‐item Prodromal Questionnaire (PQ‐16) is a versatile screen tool for routine screening of at‐risk individuals. We wished to evaluate the psychometric properties of the Italian version of the PQ‐16 (iPQ‐16) in a sample of 72 help‐seeking adolescents (age range 13‐17 years) referred to child and adolescent neuropsychiatry services for diagnostic assessment. Methods: Participants who completed iPQ‐16 were subsequently interviewed with the Comprehensive Assessment of At‐Risk Mental States (CAARMS) to confirm the psychosis high risk state. We then examined the diagnostic accuracy (sensitivity, specificity, positive and negative predictive values [PPV e NPV]) and concurrent validity between iPQ‐16 and CAARMS using Cronbach's alpha and Cohen's kappa. We also tested the validity of the adopted iPQ‐16 cut‐offs through Receiver Operating Characteristic (ROC) curves plotted against CAARMS diagnoses and the 1‐year predictive validity of the iPQ‐16. Results: Overall, the psychometric properties of the iPQ‐16 were satisfactory. The iPQ‐16 showed high internal consistency (Cronbach's alpha = .827) and acceptable diagnostic accuracy (77% sensitivity, 72% PPV) and concurrent validity (Cohen's k = 0.309). ROC analyses pointed to iPQ‐16 total distress score of ≥10 as best cut‐off. Conclusion: The iPQ‐16 is a reliable and valid instrument for routine screening of at‐risk individuals in Italian neuropsychiatry services.